Perceraian Akibat Kekerasan Dalam Rumah Tangga: Sebuah Pendekatan Feminis Pada Matius 19:9 - Renti Ardina Gajah; Haposan Silalahi; Warseto Freddy Sihombing (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
Divorce is the end of a marriage between husband and wife and they no longer live together. Divorce is also a severance of the relationship between husband and wife in faith and the blessing of not being together again to seek their respective lives. Many people have divorced, even though we know that divorce is strictly prohibited in Christianity. In the Bible, divorce is hated by the Lord Jesus in Matthew 19:6 which states that divorce is prohibited. The aim of this research is to find out divorce due to domestic violence: A feminist approach Matthew 19.9. In marriage, you definitely hope for a happy family full of love. Every family definitely wants their family to be safe, comfortable and always happy. However, we cannot deny that having a family is not only about happiness, but in the family it can also bring conflict due to misunderstandings or incompatibility with each other. Lack of harmony between husband and wife which can lead to domestic violence (KDRT). Domestic violence in the family is a shame that often becomes an excuse to cover up the facts of domestic violence. Those who are considered to be exposing their own family's disgrace and embarrassing themselves. The research method used in the research is qualitative research using Fiorenza's feminist interpretation approach. All research materials used in the discussion of each part of this study will be taken from the literature available in the library. A literature review includes identification, explanation of sources, and systematic description of documents containing information related to the problem to be studied. The results of this pattern renewal research provide an opportunity for women's independence to escape from the hegemony of male colonization. Jesus created equality in the relationship between husband and wife.